Requirement for Phosphoglucose Isomerase of Xanthomonas campestris in Pathogenesis of Citrus Canker - Tung, Shu Yun (American Society for Microbiology, 1999)
A mutant (XT906) of Xanthomonas campestris pv. citri, the causal agent of citrus canker, was induced by insertion of the transposon Tn5tac1 and isolated. This mutant did not grow or elicit canker disease in citrus leaves but was still able to induce a hypersensitive response in a nonhost plant (the common bean). The mutant was also unable to grow on minimal medium containing fructose or glycerol as the sole carbon source. A 2.5-kb fragment of wild-type DNA that complemented the mutant phenotype of XT906 was isolated. Sequence analysis revealed that this DNA fragment encoded a protein of 562 amino acids that shows homology to phosphoglucose isomerase (PGI). Enzyme activity assay confirmed that the encoded protein possesses PGI activity. Analysis of the activity of the promoter of the pgi gene revealed that it was inhibited by growth in complex medium but induced by culture in plant extract. These results demonstrate that PGI is required for pathogenicity of X. campestris pv. citri.